# Using the completing the square method, rewrite f(x) = x^{2} - 6x + 2 in vertex form.

**Solution:**

The vertex form of the equation is given by

f(x) = a(x - h)^{2 }+ k

Given, f(x) = x^{2} - 6x + 2

Converting to vertex form,

x^{2} - 6x + 2

= x^{2} - 6x + 9 + 2

= (x - 3)^{2 }+ 9

f(x) + 9 = (x - 3)^{2} + 2

f(x) = (x - 3)^{2} + 2 - 9

f(x) = (x - 3)^{2} - 7

Therefore, the equation in vertex form is f(x) = (x - 3)^{2 }- 7.

## Using the completing the square method, rewrite f(x) = x^{2} - 6x + 2 in vertex form.

**Summary:**

Using the completing the square method, the equation f(x) = x^{2} - 6x + 2 in vertex form is f(x) = (x - 3)^{2 }- 7.

Math worksheets and

visual curriculum

visual curriculum